1998
DOI: 10.1021/ac9711302
|View full text |Cite
|
Sign up to set email alerts
|

Diffraction-Based Cell Detection Using a Microcontact Printed Antibody Grating

Abstract: An optical detector has been fabricated that is specific for targeted bacterial cells, by stamping an antibody grating pattern on a silicon surface. The antibody grating alone produces insignificant optical diffraction, but upon immunocapture of cells, the optical phase change produces a diffraction pattern. This technique eliminates much of the surface modifications and the secondary immunochemical or enzyme-linked steps that are common in immunoassays. Microcontact printing provides an alternative to previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(57 citation statements)
references
References 17 publications
1
56
0
Order By: Relevance
“…Early studies by St. John et al demonstrated that diffraction optics can be used to detect whole bacteria cells captured using an antibody grating stamped on a silicon surface. 42 In 2005, Goh et al demonstrated the ability of diffraction optics to measure two different binding interactions simultaneously without the use of labels. To achieve this, receptor molecules mouse IgG and rabbit IgG were immobilized in two different patterns via PDMS stamping on the same 2D surface.…”
Section: Diffraction Opticsmentioning
confidence: 99%
“…Early studies by St. John et al demonstrated that diffraction optics can be used to detect whole bacteria cells captured using an antibody grating stamped on a silicon surface. 42 In 2005, Goh et al demonstrated the ability of diffraction optics to measure two different binding interactions simultaneously without the use of labels. To achieve this, receptor molecules mouse IgG and rabbit IgG were immobilized in two different patterns via PDMS stamping on the same 2D surface.…”
Section: Diffraction Opticsmentioning
confidence: 99%
“…Diffraction-based sensors (DBSs) are a novel new class of biodiagnostic sensing devices that are inexpensive, easy to operate and capable of quantifying biological analyte concentrations for a variety of systems [1][2][3][4][5]. The basic operating principle of the DBS is that biological "target" molecules are patterned onto a substrate surface in the form of a diffraction grating.…”
Section: Introductionmentioning
confidence: 99%
“…Diffraction is an old concept, and its use in the detection of analytes has recently been investigated [1,2,3]. Diffraction occurs due to the wave nature of light: when light hits a non-random pattern of obstacles, the resulting constructive and destructive interference will result in a clear diffraction image.…”
Section: Introductionmentioning
confidence: 99%